Systematic review of studies about countertransference in adult psychotherapy - Diogo de Bitencourt Machado (Trends in Psychiatry and Psychotherapy, 2014)
Introduction: Countertransference, the emotional reaction of a psychotherapist toward a patient, is an important technical element of psychotherapy. The purpose of this systematic review was to identify and describe the main findings of studies that evaluated countertransference in adult psychotherapy. Methods: A search was conducted of the databases Embase, PubMed, PsycINFO and Web of Knowledge to retrieve data published in any language at any time. Results: Of the 1,081 studies found in the databases, 25 were selected. Most were about psychodynamic psychotherapy, and results indicated that positive countertransference, that is, feelings of closeness to the patient, are associated with positive outcomes, such as symptom improvement and good therapeutic alliance. Conclusions: Although few studies were found in the literature, countertransference seems to be an important source of knowledge about several aspects, such as treatment outcomes, attachment style, therapeutic alliance, patient symptoms and diagnoses.